2022
DOI: 10.1016/s0140-6736(22)00112-x
|View full text |Cite
|
Sign up to set email alerts
|

High-dose immunoglobulins from convalescent donors for patients hospitalised with COVID-19

Abstract: MS has received grant support from Astellas Pharmaceuticals and Biotest to her institution, Saarland University, outside the area of work commented on here, and honoraria for lectures from Biotest and Novartis. SLB has received travel grants and speaker fees from Astellas Pharmaceuticals, Becton Dickinson, Novartis, Pfizer, and Shionogi outside the area of work commented on here, and participated on advisory boards of Pfizer (pertaining to ceftazidime/avibactam) and Shionogi (pertaining to cefiderocol).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The antibody treatment approach has thus far demonstrated efficacy at an earlier stage, namely pre‐hospitalization, of the disease through trials with monoclonal antibodies. This was not something that was so apparent when the clinical trial was designed and warrants more research for better understanding [ 54 , 55 , 56 , 57 ].…”
Section: New Plasma Products and Supplymentioning
confidence: 99%
“…The antibody treatment approach has thus far demonstrated efficacy at an earlier stage, namely pre‐hospitalization, of the disease through trials with monoclonal antibodies. This was not something that was so apparent when the clinical trial was designed and warrants more research for better understanding [ 54 , 55 , 56 , 57 ].…”
Section: New Plasma Products and Supplymentioning
confidence: 99%
“…The study has also identified an increase in adverse events (particularly respiratory failure) in patients with neutralizing antibodies receiving the HIG, versus those without antibodies [19] . This observation raises questions on the possible negative effects of the administration of anti-SARS-CoV-2 HIG in patients with pre-existing neutralizing antibodies [87] . These adverse events do not seem specific to a particular brand of anti-SARS-CoV-2 HIG since this study used 4 different products.…”
Section: Safety and Efficacy Of Anti-sars-cov-2 Hyperimmune Immunoglo...mentioning
confidence: 99%
“…10,11 Accordingly, patients at this stage of strong viral burden and inflammation become unresponsive to passive immunotherapy with specific mAbs or convalescent plasma. 12,13 Immune dysfunction is clearly multifactorial in ICU patients, with atypical myeloid cell expansion and increased levels of pro-inflammatory cytokines correlating with T cell lymphocytopenia and a broad T cell activation including Th1, Th2, Th17, and MAIT cells. [14][15][16][17][18][19] Cellular anomalies are also present on the B-cell side, and differ between patients with mild COVID-19 and ICU patients, the latter showing an increase of blood plasma cells and of double-negative (DN) [IgD neg , CD27 neg ] B-cells suggesting extra-follicular B-cell activation.…”
Section: Introductionmentioning
confidence: 99%